A scalar conditional in Greek: looking for the consequent - Oikonomou, Despina (Proceedings of Sinn und Bedeutung, 2020)
This paper discusses a construction with a conditional interpretation in Greek which differs from “typical” conditionals in interesting ways. I refer to this construction as pu- conditional, since it is always introduced with the particle pu whose semantic contribution is to be analysed. Pu-conditionals only appear with subjunctive mood and they do not combine with a consequent as typical conditionals. Instead, the meaning of the consequent is implied and indicates that if the prejacent holds, a contextually supplied scalar property will hold to a higher degree.